Size effect on fire resistance of structural concrete. (15th September 2015) - Reddy, Dronnadula V.; Sobhan, Khaled; Liu, Lixian; Young, Jody D.
Highlights: Size effect on fire resistance by integrating thermal and structural similitudes. Numerical analysis and structural fire testing performed on reinforced concrete. Relationships between specimen size and fire endurance, load capacity, cover thickness. Fire endurance increases with cross-section size and concrete cover thickness. Abstract: Research on the size effect of reinforced concrete members at ambient temperatures includes only limited studies on the size effect of their fire resistance, integrating thermal and structural similitudes. Preliminary testing on concrete cylinders and unreinforced beams showed a ¼ ASTM E-119 exposure time for the fire rating of small scale specimens compared to the full scale ones. Based on numerical and experimental analyses at Florida Atlantic University, the following quantitative relationships were developed for columns and beams: (i) equivalent fire duration and specimen size; (ii) fire endurance and cross-section size, and (iii) cross-section size, concrete cover thickness, and load capacity after fire exposure. The fire endurance at similar load ratios increases with an increase of member cross-section size and concrete cover thickness.